Marketing mix drivers of clients satisfaction in technology-enabled service: Study of Nigerian GSM subscribers - Ahmad, Aminu; Ahmad, Hartini (IBIMA Publishing, 2008)
Rapid diffusion of mobile telephone services is accompanied with low satisfaction and high switching behavior many markets.Despite the popularity of technology diffusion studies in marketing literature, limited research concentrate on the impact of marketing mix variables vis-à-vis clients’ satisfaction. Much fewer studies were conducted in developing nations.This paper investigates the influence of marketing mix on clients’ satisfaction with innovation adoption in Nigerian GSM market.Building on Technology Adoption Life-Cycle Model and extensive literature review, six constructs were theoretically developed and statistically validated.Multiple regression run on a sample of 373 subscribers drawn from four universities, indicates the five marketing mix variables predict 52% of the variance on clients’ satisfaction.Furthermore beta coefficients revealed Core Service (0.38) makes the strongest unique contribution in explaining clients’ Satisfaction followed by Pricing at 0.22, while Distribution (0.072) is the only variable not making significant contribution to the model.